Binding modes of the KRAS(G12C) inhibitors GDC-6036 and LY3537982 revealed by all atom molecular dynamics simulations - Leini, Renne; Kapp, Jonas; Kopra, Kari; Pantsar, Tatu (NATURE PORTFOLIO, 2026)
Over 100 co-crystal structures of KRAS switch-II pocket (SII-P) targeting inhibitors are currently available in the RCSB Protein Data Bank. These publicly available structures are invaluable tools that have led to a more in-depth understanding of KRAS SII-P pocket, which is crucial for targeted drug design efforts. The binding modes (co-crystal structures) of two KRAS(G12C) inhibitors that have advanced to the clinical trials, GDC-6036 (divarasib) and LY3537982 (olomorasib), are currently unavailable. Here, we reveal the putative binding modes of these two G12C inhibitors by utilizing the available structural data of analogous compounds and molecular dynamics (MD) simulations (total simulation time of 200 micros). Our biochemical assays confirm high affinity of both inhibitors for KRAS(G12C), with differential susceptibility to typical resistance associated co-mutations. A co-mutation at Tyr96 reduces the affinity of both inhibitors, whereas a mutation at His95 negatively impacts only GDC-6036. While both inhibitors display low activity towards KRAS(WT), LY3537982 maintains high activity against other RAS isoforms with G12C mutation. As the simulation predictions align with the experimental results, our findings indicate that microsecond timescale simulations can be a valuable tool for predicting binding modes.